Application of the Crime of Endangering Public Safety by Dangerous Methods: Implications for Epidemic Prevention and Control in Sports and Community Settings - Yifang Wang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The extraordinary circumstances following the outbreak of COVID-19 have heightened the application of laws addressing the crime of endangering public safety by dangerous methods, particularly in epidemic-related offenses. However, challenges persist in distinguishing this crime from other epidemic-related offenses, securing convictions, and aligning with administrative penalties. This study examines the constitutive elements of the crime, addressing the new legal and practical issues arising from its application during the pandemic and analyzing its evolving characteristics in epidemic-related cases. The discussion focuses on four key components—objective elements, object elements, subjective elements, and subject elements—providing a comprehensive framework for understanding the application of this crime. Within the context of sports and community environments, these insights are particularly relevant for ensuring public safety during events and managing risks associated with disease prevention and control. By offering guidance for the practical judgment and application of this crime, this research underscores the importance of legal and psychological frameworks in fostering safe and responsible practices in sports and community settings during health crises.